2018
DOI: 10.1155/2018/3504245
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Initial Endodontic Treatment Performed, by One Specialist, in 122 Tunisian Patients: A Retrospective Study

Abstract: Objective To assess the 6- to 24-month outcome of endodontic treatments performed, by one specialist, and to identify prognostic factors that may influence initial endodontic treatment outcome (IETO). Methods One hundred and forty-six patients out of 163 were included. A number of 201 teeth were endodontically treated, and an overall number of 408 canals were obturated. Of these, 165 teeth received initial endodontic treatment (IET). The criteria of the European Society of Endodontology were used to assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 54 publications
3
5
1
Order By: Relevance
“…In this investigation, the adequate length for endodontists was noted in 74.48%, which is in agreement with other research [ 26 ], but it is in contrast with others showing higher (86–93.55%) [ 28 , 29 ] or lower percentages (41.2–62.5%) [ 27 , 47 ]. Similarly to these results, the adequate quality of root fillings (length and density) performed by Australian endodontists was found in 77.4–91.0% [ 30 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this investigation, the adequate length for endodontists was noted in 74.48%, which is in agreement with other research [ 26 ], but it is in contrast with others showing higher (86–93.55%) [ 28 , 29 ] or lower percentages (41.2–62.5%) [ 27 , 47 ]. Similarly to these results, the adequate quality of root fillings (length and density) performed by Australian endodontists was found in 77.4–91.0% [ 30 ].…”
Section: Discussionsupporting
confidence: 92%
“…These discrepancies can be related to different NiTi rotary systems, obturation methods (lateral condensation of cold gutta-percha vs. single cone technique) and number of operators who performed RCT (one vs. more). In the present study, the short-filling of root canals among endodontists was reported in 3.28% of cases, similarly to others [ 26 , 28 ]. However, it is in contrast with the studies where mainly posterior teeth were treated (short-filling in 17.7–18.8%) [ 27 , 47 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Factors selected for such an evaluation may be more or less restrictive. In general terms, various studies base their analyses on one to three factors [ 3 , 12 , 13 , 14 , 15 , 16 , 17 ], while others assess the influence of multiple factors, taking into account preoperative, intraoperative, and postoperative factors [ 7 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. The latter is the case of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the influence of intraoperative complications in RCT outcomes, such as instrument fractures, perforations, apical stops or seats, or a failure to achieve patency, no clear association is found among various studies [ 22 , 40 , 43 , 50 ]. Others, however, reported that they negatively influence the RCT outcome [ 34 , 38 ].…”
Section: Discussionmentioning
confidence: 99%